KOMPONEN SENYAWA BIOAKTIF EKSTRAK BINTANG LAUT Protoreaster nodosus Dan Linckia laevigata DENGAN METODE MASERASI - Mailoa, Meigy Nelce; Leiwakabessy, Jusuf; Chakti, Arini Padma Widya (Program Studi Pendidikan Biologi FKIP Unpatti, 2023)
Background : One type of species from the class Asteroidea phylum Echinodermata, namely sea stars. Approximately 6000 species from the Phylum Echinodermata and all live in the sea. The use of starfish by the community is still very limited, where it is only used as a food source, even though starfish can also be used as a source of bioactive compounds that are more economically valuable so that they can be used for development in the food and health sectors. This study aims to determine the content of bioactive compounds from the extracts of sea stars Protoreaster nodosus and Linckia laevigata. Methods: Samples were obtained from Waisarisa waters on Seram Island, analysis was carried out at the Biochemistry Laboratory, Department of Chemistry, Faculty of Mathematics and Natural Sciences, University of Pattimura. The parameters tested in this study were phytochemical tests which included flavanoid tests, saponin tests, steroid tests, tannin tests and phenolic tests. The extraction technique was carried out by maceration with ethanol solvent. Results: The results of the phytochemical test of the starfish extract Protoreaster nodosus which had positive results in the phytochemical test were tannins, phenolics and saponins. While the test results on the Linckia laevigata starfish extract which had positive results found bioactive flavonoids and saponins. Conclusion: The results of the phytochemical screening test of Protoreaster nodosus star extract have 3 bioactive components namely flavonoids, tannins, phenolics and saponins.